Forensic Accounting and Investigative Auditing, and Their Implications for Fraud Disclosure (Survey of the Financial and Development Supervisory Agency (BPKP) of West Java Province) - Muhammad Ali; Yessika Rizki Amelia (Tirtayasa Ekonomika, 2025)
The purpose of this study is to determine the effect of forensic accounting and investigative auditing in disclosing fraud at the Financial and Development Supervisory Agency (BPKP) of West Java Province. This study was motivated by the rampant cases of fraud that occurred, so that a strategic tool is needed that can help in disclosing fraudulent acts. This study uses a quantitative method, where data is collected through a questionnaire compiled with a Likert scale. The Population in this study were auditors who had an understanding and/or experience of investigative audits at the BPKP of West Java Province. With a sample size of 37 respondents, using a saturated sampling technique (census). Based on the results of the partial test analysis, it is known that forensic accounting has no influence on disclosing fraud. While investigative audits have an influence on disclosing fraud. The results of simultaneous testing state that both variables together have an influence on disclosing fraud.